Sars-Cov-2: The First Wave of Disease Outbreak and Its Barriers to Chronic Diseases Management - Virgílio Garcia Moreira; Ana Cristina Canedo; Renato Gorga Bandeira de Mello (Brazilian Society of Geriatrics and Gerontology, 2024)
None.